STUDY ON THE ROLE OF URBAN FOREST TOWARD TEMPERATURE REDUCTION IN RESIDENTIAL AREA - Marlina, Etty; Jaya, I Nengah Surati; Wijanarto, Antonius B (MAJALAH ILMIAH GLOBE, 2010)
Nowadays, the quality of urban environment is a challenging problem. Urban development indicated by the increase of population as well as development in all aspects, either positive or negative. But it can degrade the environment quality. This can be indicated by for example, air pollution, which can reduce the oxygen supply and overwhelms the production of carbon dioxide as well as the increase in temperature. From the foregoing problems, the âback to natureâ concept is needed to solve environment problem in urban area, by introducing the urban forest. However, constraints in available space exists, therefore, alternative solution can be employed by increasing the effectiveness of existing urban forest. This research aims at analyzing the effectiveness of urban forest in reducing the air temperature based on two parameters: forest structures and forest forms. Keywords: Urban Forest, Temperature Reduction, Forest Structure, Forest Forms, GIS Analysis.Â ABSTRAKKualitas lingkungan perkotaan, akhir-akhir ini, merupakan masalah yang menantang. Perkembangan perkotaan selalu mengindikasikan dengan pencemaran udara dan perkembangan di segala bidang, yang berdampak positif maupun negatif. Namun demikian, perkembangan ini dapat menurunkan kualitas lingkungan. Hal ini dapat diindikasikan misalnya polusi udara, yang dapat menurunkan jumlah oksigen dan meningkatkan jumlah karbon dioksida yang juga terindikasikan dengan naiknya suhu udara perkotaan. Dari berbagai masalah lingkungan tersebut, konsep kembali ke alam dibutuhkan untuk mengatasi masalah lingkungan perkotaan, dengan mengenalkan konsep hutan kota. Namun, banyak pembatasan-pembatasan termasuk lahan yang tersedia, sehingga solusi yang dapat meningkatkan efektivitas hutan kota dibutuhkan. Penelitian ini menganalisa efektivitas hutan kota dalam menurunkan suhu udara perkotaan berdasarkan dua parameter: struktur hutan dan bentuk hutan.Kata Kunci: Hutan Kota, Penurunan Suhu Udara, Struktur Hutan, Bentuk Hutan, Analisa SIG.